Validation of an instrument to measure corporate social responsibility in consumers of Mexico (2016)
The current study aimed to evaluate the empirical sustainability of a measurement instrument of corporate social responsibility in consumers from Mexico. For this purpose, a non-probabilistic sample of 436 students of a public university was selected, which was divided into two subsamples (n = 218). By means of an exploratory factor analysis and a confirmatory factor analysis, the results obtained showed the empirical validity of the model. It is proposed that by using this instrument, sufficient empirical information might be obtained that serves for making strategic decisions, as well as to enrich and sustain the ideas and existing theories on CSR, which many of them have not been validated within the Latin American context. It is important to note that due to the nature of the topic and the type of scale, there exists the possibility of certain social desirability in the instrument responses. It is concluded that the instrument can be used by other researchers to assess CSR in a sustainable manner